Not just a gut feeling: a deep exploration of functional bacterial metabolites that can modulate host health - Andrew Gold; Jiangjiang Zhu (Gut Microbes)
Bacteria have been known to reside in the human gut for roughly two centuries, but their modulatory effects on host health status are still not fully characterized. The gut microbiota is known to interact with dietary components and nutrients, producing functional metabolites that may alter host metabolic processes. The majority of thoroughly researched and understood gut microbial metabolites fall into two categories: short-chain fatty acids (SCFAs) and bacterial derivatives of dietary tryptophan. Despite the heavy emphasis on these metabolites, other metabolites stemming from microbial origin have significant impacts on host health and disease states. In this narrative review, we summarize eight recent studies elucidating novel bacterial metabolites, detailing the process by which these metabolites are identified, their actions within specific categories of human health, and how diet may impact production of these metabolites. With similar future mechanistic research, a more complete picture of bacterial impact on host metabolism may be constructed.